Honduras : Debt Sustainability Analysis 2006. (IMF Staff Country Reports; Country Report ;, 2006)
In the IMF staff's view, Honduras's debt is subject to a moderate risk of distress. The framework follows a methodology for assessing the risk of debt distress in low-income countries (LICs), guided by indicative, country-specific external debt burden thresholds derived from the empirical finding that sustainable debt levels for LICs increase with the quality of policies and institutions. The debt sustainability analysis (DSA) is based on various assumptions. The evolution of the domestic debt has also improved. Two major exogenous factors and one policy assumption underlie the macroeconomic framework of the baseline scenario.